2022
DOI: 10.3390/cells11142222
|View full text |Cite
|
Sign up to set email alerts
|

Role of Immuno-Inflammatory Signals in Liver Ischemia-Reperfusion Injury

Abstract: Ischemia reperfusion injury (IRI) is a major obstacle in liver resection and liver transplantation. The initial step of IRI is mediated through ischemia which promotes the production of reactive oxygen species in Kupffer cells. This furthermore promotes the activation of pro-inflammatory signaling cascades, including tumor necrosis factor-alpha, IL-6, interferon, inducible nitric oxide synthase, TLR9/nuclear-factor kappa B pathway, and the production of damage-associated molecular patterns (DAMPs), such as ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Therefore, we analyzed the function of the significantly differentially expressed target genes to gain a preliminary understanding of the potential function of the differentially expressed lncRNAs. In the Biological Process ontology category of GO enrichment analysis, DEGs were mostly enriched in cellular divalent inorganic cation homeostasis, response to molecule of bacterial origin, response to lipopolysaccharide, regulation of body fluid levels, and hormone metabolic process, which is consistent with the previously known pathophysiological mechanisms of post‐transplantation HIRI 40,41 . Apart from this, KEGG enrichment analysis revealed that DEGs were mostly enriched in the PI3K‐Akt signaling pathway, focal adhesion, Hippo signaling pathway, TNFα signaling pathway, etc 42 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, we analyzed the function of the significantly differentially expressed target genes to gain a preliminary understanding of the potential function of the differentially expressed lncRNAs. In the Biological Process ontology category of GO enrichment analysis, DEGs were mostly enriched in cellular divalent inorganic cation homeostasis, response to molecule of bacterial origin, response to lipopolysaccharide, regulation of body fluid levels, and hormone metabolic process, which is consistent with the previously known pathophysiological mechanisms of post‐transplantation HIRI 40,41 . Apart from this, KEGG enrichment analysis revealed that DEGs were mostly enriched in the PI3K‐Akt signaling pathway, focal adhesion, Hippo signaling pathway, TNFα signaling pathway, etc 42 .…”
Section: Discussionsupporting
confidence: 78%
“…Hua et al 39 the previously known pathophysiological mechanisms of posttransplantation HIRI. 40,41 Apart from this, KEGG enrichment analysis revealed that DEGs were mostly enriched in the PI3K-Akt signaling pathway, focal adhesion, Hippo signaling pathway, TNFα signaling pathway, etc. 42 Some of these pathways have been recognized as canonical pathways associated with HIRI.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic HMGB1 is further increased in the damaged hepatocytes in the centrilobular area on day 1. Released HMGB1 stimulates monocytes/macrophages through the cell-surface receptors such as TLRs (in particular, TLR2, TLR4, and TLR9) and RAGE 54 , 81 , 82 , 83 , 84 , 89 . An increased expression of TLR-4 is confirmed in the TAA-induced liver lesion 54 .…”
Section: Macrophage-related Events In the Early Stage Of Chemical-ind...mentioning
confidence: 99%
“…In ammatory responses play key roles in the initiation and progression of hepatic I/R injury [19]. Since KLF6 has been shown to be involved in in ammatory responses [20], we next investigated whether KLF6 affected the in ammatory response after hepatic I/R injury in mice.…”
Section: Klf6 De Ciency Exacerbates Hepatic I/r Injurymentioning
confidence: 99%